A perovskite solar cell textile that works at −40 to 160 °C. Issue 11 (4th March 2020) - Xu, Limin; Fu, Xuemei; Liu, Fei; Shi, Xiang; Zhou, Xufeng; Liao, Meng; Chen, Chuanrui; Xu, Fan; Wang, Bingjie; Zhang, Bo; Peng, Huisheng
Abstract : A wearable solar cell textile that works at −40 to 160 °C has been achieved by designing a compact perovskite layer on aligned TiO2 nanotubes to act as a stress buffer layer on fiber electrode surfaces. Abstract : Environmental adaptability is an important factor in the practical application of flexible solar cells. This is particularly important in fiber-based solar cell textiles that are recently attracting increasing interest to solve application problems in a variety of emerging important fields such as in wearable and portable electronics. However, the difficult preparation of a compact active thin layer on a curved fiber surface and the interface instability under varying temperatures have largely limited the development of solar cell textiles. Here, we have made novel perovskite solar cell textiles by depositing a thin and continuous perovskite layer on aligned titanium dioxide nanotubes of fiber electrodes, and the aligned titanium dioxide nanotubes also functioned as an effective stress buffer layer for high interface stability. The power conversion efficiencies remained unchanged during storing at −20 or 100 °C for 240 h, and they could also be well maintained by 90% at a working temperature range of −40 to 160 °C.